2021
DOI: 10.3390/cancers13143551
|View full text |Cite
|
Sign up to set email alerts
|

Claisened Hexafluoro Inhibits Metastatic Spreading of Amoeboid Melanoma Cells

Abstract: Metastatic melanoma is characterized by poor prognosis and a low free-survival rate. Thanks to their high plasticity, melanoma cells are able to migrate exploiting different cell motility strategies, such as the rounded/amoeboid-type motility and the elongated/mesenchymal-type motility. In particular, the amoeboid motility strongly contributes to the dissemination of highly invasive melanoma cells and no treatment targeting this process is currently available for clinical application. Here, we tested Claisened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Broaching the topic of melanoma plasticity and metastasis, two of the main characteristics of melanoma cells, and explaining the aggressiveness and treatment failures of melanoma patients, Leo et al report that Claisened Hexafluoro, a chemical analogue of Honokiol, inhibits melanoma cells spreading by blocking amoeboid-type motility and, in fine, melanoma metastasis capacities [7]. Mechanistically, authors have shown that Claisened Hexafluoro inhibits mitochondrial activity, leading to an activation of AMPK.…”
mentioning
confidence: 99%
“…Broaching the topic of melanoma plasticity and metastasis, two of the main characteristics of melanoma cells, and explaining the aggressiveness and treatment failures of melanoma patients, Leo et al report that Claisened Hexafluoro, a chemical analogue of Honokiol, inhibits melanoma cells spreading by blocking amoeboid-type motility and, in fine, melanoma metastasis capacities [7]. Mechanistically, authors have shown that Claisened Hexafluoro inhibits mitochondrial activity, leading to an activation of AMPK.…”
mentioning
confidence: 99%